Designing an Optimal Education and Training Model for Relationship Manager BRIguna BRI West Indonesia Region - Baskoro, Fajar; Pancakusuma, Muhammad Bayu; Raharjo, Susilo Toto (Research Horizon, 2025)
The rapid advancement of digital technology and shifts in consumer behavior have driven the banking industry, including Bank Rakyat Indonesia (BRI), to adapt by enhancing the capabilities of its human resources (HR). In this context, it is crucial to develop an effective education and training framework for BRI employees, particularly RM Briguna, to remain competitive in the digital era. This study focuses on assessing the education and training requirements of RM Briguna employees in the digital age and creating a tailored model that meets the specific needs of workers, especially those in western Indonesia. Using a qualitative methodology, the research incorporates a literature review analyzing various training models utilized in the banking sector and examines best practices in HR development. The findings highlight that effective training approaches include competency-based programs, on-the-job training, e-learning, blended learning, and gamification. Each model presents distinct benefits and limitations, which must be carefully evaluated during the design process. An analysis of existing training initiatives reveals a need for updates in curricula and methods to align with industry demands and emerging technological trends. The ideal education and training framework should prioritize flexibility, innovation, and alignment with employees' unique needs. Strategic investment in HR development and collaboration with educational institutions will play a vital role in equipping BRI to tackle digital-era challenges. By implementing an optimized training model, BRI can cultivate a skilled and adaptable workforce—particularly RM Briguna in western Indonesia—capable of driving the company’s growth and success.